The current situation and the attitudes of judicial officials in Greece regarding their training needs - Karypidou, Maria; Kofidou, Christina; Folinas, Dimitris; Mylonas, Dimitris; Fragkaki, Zafeiro (LPPM Universitas Malikussaleh, 2023)
The education and training of the judiciary is an issue that concerns the quality and efficiency of the judicial system. The aim of this research is to investigate the current situation and attitudes of judicial officers of the criminal-civil courts, administrative courts, and prosecutors' offices in Greece regarding their training and education. They received this training both during their first period of appointment (introductory training) and during their period of service (continuing training). There is very little research on the training and education of judicial officials in Greece, which makes this research necessary. An online structured questionnaire, consisting of seven sections, was designed for the needs of the survey, which was answered by 273 respondents. The results of the survey indicate the absence of organized training by the judicial officers' branch, as well as the increase in the performance and effectiveness of judicial officers when they are trained. Finally, possible solutions and improvements for the education-training policy of judicial officials are proposed.